Tones and traits - experiments of text-based extractions with cognitive services - Ulla Gain; Virpi Hotti (Finnish Social and Health Informatics Association, 2017)
Cognitive services mimic brain mechanisms by the algorithms, for example, extracting emotions, language styles, and social tendencies from text. The cognitive services offer the inferred insights that are even more detailed than the observation-based ground-truth data. In this paper, the text-based extractions are utilized by the cognitive services (i.e., Microsoft's Text Analytics and IBM's AlchemyLanguage, Natural Language Understanding, Personality Insights and Tone Analyzer). The tones (i.e., emotions, language styles and social tendencies) and personality traits (i.e., social tendencies, needs and values) are extracted from a web-site document with no time by the cognitive services the algorithmic functionality of which are exemplified. Both the tones and personality traits are the inferred insights that can be used to assess the personality. Finally, 47 personality traits are tabulated to illustrate the trait-based questions that can be used in the interventions.